Development and application of metal chelate-epoxy bifunctional loofah sponge for the purification and immobilization of recombinant trehalose synthase. (May 2022) - Chang, Jui-Chia; Chen, Yi-An; Lin, Sung-Chyr
Abstract: The preparation and application of metal chelate-epoxy bifunctional loofah sponge for the selective adsorption and covalent immobilization of a His-tagged trehalose synthase were reported. The adsorption of the His-tagged trehalose synthase on the metal chelate loofah sponge was found to follow the Langmuir isotherm model with Co 2+ ion exhibiting an adsorption capacity of 1.183 mg/g and a superior selectivity over the other metal ions tested. Bifunctional loofah sponge, designated as BiFLS57, with an adsorption capacity of 0.639 mg/g and an [epoxy groups]/[metal chelate groups] ratio of 0.75 was used for enzyme immobilization. The ideal incubation conditions for the selective adsorption and covalent immobilization of the His-tagged trehalose synthase were 1.0 h at 4 °C and 16 h at 30 °C, respectively. The immobilized enzyme thus prepared exhibited an enzyme activity of 3.99 U/g with a 93% immobilization yield and an 84% global activity yield. The immobilized enzyme prepared with the metal chelate-epoxy bifunctional loofah sponge BiFLS57 exhibited superior thermostability and operational stability in a repeated-batch process, retaining 96% of its initial activity after 20 cycles. The employment of the metal chelate-epoxy bifunctional loofah sponge can significant facilitate enzyme immobilization processes by consolidating protein purification and enzyme immobilization steps. Graphical Abstract: ga1 Highlights: Metal chelate-epoxy bifunctional loofah sponges were prepared. Selective adsorption by the bifunctional loofah sponge was investigated. The time required for covalent immobilization was determined as 16 h. Enzyme immobilized on bifunctional loofah sponge exhibited superior stability.